Anxiety Coping for High-Achieving Students in Elite Academic Environments: From Self-Consciousness to Self-Awareness - Nan Su (Lecture Notes in Education Psychology and Public Media, 2026)
The transition to elite academic institutions often presents significant psychological challenges for high-achieving students, who must navigate heightened competition and shifting self-concepts. After entering highly competitive elite campuses, numerous high-achieving students are prone to psychological adaptation issues including identity confusion, anxiety and even depression. Based on the literature review method, this paper sorts out the causes of anxiety among this group from three dimensions: neurodevelopmental imbalance, overreliance on external labels and hidden competition induced by a single evaluation system. It analyzes the logical transition of students' self-cognition from passive to rational, and proposes practical educational strategies from cognitive, behavioral, and environmental perspectives to build an intervention pathway of Identification-Acceptance-Transformation. It include establishing multidimensional evaluation systems, promoting emotional awareness and cognitive restructuring, and implementing progressive task challenges with reflective mechanisms. By fostering self-awareness rather than self-consciousness, the proposed framework not only alleviates academic anxiety but also supports sustainable personal growth and resilience.